Influence of Operating Conditions on Reuterin Production Using Resting Cells of Limosilactobacillus reuteri DPC16 - Sun Y; Gutierrez-Maddox N; Mutukumira AN; Maddox IS; Shu Q (MDPI (Basel, Switzerland), 2022)
Limosilactobacillus reuteri strains can secrete a potentially valuable chemical and broadspectrum antimicrobial substance named reuterin (3-hydroxypropionaldehyde, 3-HPA). L. reuteri DPC16 is a novel and patented probiotic strain that is used commercially because of its proven ability to kill various foodborne pathogens. A two-step process has been developed for reuterin production from glycerol using L. reuteri DPC16. Cells were grown, followed by harvesting, and then were incubated with glycerol for reuterin production. Parameters investigated during the glycerol conversion included the initial glycerol concentration, the biomass concentration, pH, culture age at harvesting, conversion time, and temperature. The highest reuterin yield was obtained using 21 g/L 24 h old cells, to convert glycerol solution (300 mmol/L) in 1 h at 30◦ C and pH 6.2. The most efficient transformation of glycerol to reuterin was achieved in approximately 20 h of growth of cells at 25◦ C and pH 6.8. Using the regression equation of this study, the maximum concentration of reuterin can be obtained using 25 g/L 20 h old DPC6 cells to ferment 350 mmol/L glycerol (initial concentration) for 2 h at 25◦ C and pH 6.8 The ranking of effects on reuterin production for the six single factors was glycerol concentration > pH > conversion time > biomass concentration > temperature > culture age.
Keywords: Limosilactobacillus reuteri DPC16; reuterin; 3-hydroxypropionaldehyde; bioconversion; probiotics